Influence of the Chemical Composition in the Electrochemical Response of Permanent Magnets - S. Godavarthi; J. Porcayo-Calderon; E. Vazquez-Velez; M. Casales-Diaz; D. M. Ortega-Toledo; L. Martinez-Gomez (Journal of Spectroscopy)
The corrosion behavior of permanent magnets with different chemical composition was evaluated. Permanent magnets were tested in 3.5% NaCl solution at room temperature using electrochemical technics such as polarization curves, open-circuit potential, linear polarization resistance, and electrochemical impedance spectroscopy measurements. Results have shown that corrosion rate is affected by Nd, Pr, and Co content. Analysis by scanning electron microscopy has shown that pitting attack is the main mode of degradation of the magnets, while Co addition reduces it and Pr addition increases it.